The peculiarities of repetition in the texts of Ukrainian spells (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to the research of lexical and syntactic repetition in the texts of Ukrainian folk spells. We analyzed the peculiarities of functioning of these kinds of repetition as a structural-semantic means of the text organization. We learned logical content, grammatical reasons of using repetition in the structure of spells.
Keywords: lexical and syntactic repetition; semantics; Ukrainian spells; text